Action against invasive species: Charcoal production, beekeeping, and Prosopis eradication in Kenya - Tabe-Ojong, Martin Paul Jr. (Elsevier, 2023)
Prosopis juliflora is an invasive alien leguminous tree introduced as a way of combating desertification, deforestation, and improving soil fertility. Over time, the tree has reported significant negative externalities to farmers. Different strategies such as management through utilization and complete eradication have been proposed to reduce these externalities. We investigate the various factors associated with adherence to these strategies. In the first place, we assess the correlates of charcoal production, beekeeping, and willingness to completely eradicate Prosopis. We then examine the welfare effects of charcoal production and beekeeping. We use survey data from 530 smallholder households in the Baringo county of Kenya who are currently contending with infestation from the invasive tree. Besides other factors, we show that a positive perception about Prosopis invasion increases the probability of engaging in charcoal production and is adversely related to beekeeping and the willingness to completely eradicate Prosopis. Delving into welfare and poverty effects of these activities, we find charcoal production to be income increasing. We argue that a blend of both management and eradication of Prosopis could offer a win-win solution to both improving the welfare and socio-economic conditions of households while also ensuring environmental and ecological safeguards, with implications for broad-based sustainability.